Unstable Political Climate, Brain Drain and Development - LOUBAKI, DIANA (Advances in Social Sciences Research Journal, 2015)
The aim of this article is to study development when political climate is unstable like during forthcoming presidential elections in poor countries. The economic agents fear for their life and thus, on the one hand, the skilled labor increases his incentives to invest in human capital accumulation in order to leave abroad in a more developed country, the brain drain is stimulates. In contrast, the unskilled labor increases his savings in order to migrate to rural regions since violence occur in big cities, dualism emerges in the economy. Indeed, depending on the level of the unstable political climate parameter, the economy admits multiple equilibria where brain drain and dualism may vary and leads the economy inside a poverty trap or to development sustainability described by an inverted U-shape curve. Indeed, this article provides theoretical foundations explaining the impact of political climate on economic development in poorest developing countries.